FEASIBILITY OF SALTED FISH ON SUMBER JAYA KAMPUNG MELAYU DISTRIK IN BENGKULU CITY - Reswita Reswita (Jurnal Agroindustri, 2014)
The aims  the research was to analysis feasibility  of salted fish  on Kampung Melayu  distrik in Bengkulu City. The responden in the research was 20 processor salted fish. Analisys method is income analysis, R/C ratio, and ROI (Return of Investment). The result showed that Income from salted fish is Rp. 134.457,15, R/C ratio  is 1,2, and ROI 9,7%. From the research can be concluded  that the salted fish business was feasible to carry on based on.